2017 Conference on Lasers and Electro-Optics Europe &Amp; European Quantum Electronics Conference (CLEO/Europe-EQEC) 2017
DOI: 10.1109/cleoe-eqec.2017.8086799
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond delays in molecular photoionization

Abstract: We report measurements of energy-dependent attosecond photoionization delays between the two outer-most valence shells of N2O and H2O. The combination of single-shot signal referencing with the use of different metal foils to filter the attosecond pulse train enables us to extract delays from congested spectra. Remarkably large delays up to 160 as are observed in N2O, whereas the delays in H2O are all smaller than 50 as in the photon-energy range of 20-40 eV. These results are interpreted by developing a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…How do the sophisticated twophoton transition elements relate to symmetry breaking in the full atomic system, including the laser field coupling in a long-range Coulomb potential, transitions involving the continuum electron, and the accurate atomic potential which is polarized by the NIR field? Additionally, our experimental methods provide a state-of-the-art approach which can investigate and manipulate symmetry-resolved photoemission dynamics on an attosecond time scale, including shape resonances dominated by high-angular-momentum continuum waves 9,10,19 , constructive and destructive interference between multiple coupled states 41 , and correlated shake-up and shake-off double ionization assisted by Auger decay 18,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How do the sophisticated twophoton transition elements relate to symmetry breaking in the full atomic system, including the laser field coupling in a long-range Coulomb potential, transitions involving the continuum electron, and the accurate atomic potential which is polarized by the NIR field? Additionally, our experimental methods provide a state-of-the-art approach which can investigate and manipulate symmetry-resolved photoemission dynamics on an attosecond time scale, including shape resonances dominated by high-angular-momentum continuum waves 9,10,19 , constructive and destructive interference between multiple coupled states 41 , and correlated shake-up and shake-off double ionization assisted by Auger decay 18,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques have been applied to a wide range of attosecond time-resolved photoelectron emission dynamics in atoms [6][7][8] , molecules [9][10][11] and even condensed matters [12][13][14][15] . Studies have demonstrated the photoelectron emission time delays arising from different ionization shells [16][17][18] , shape resonances 9,10,19 , electron correlation 20 , orbital asymmetry 21 , spatial asymmetry (chirality) 11 , and electron delocalization 22 . These time delays are attributed to the energy dependence of the scattering phase shift during electron transitions in a short-range potential and the laser field coupling effect in the continuum 23,24 .…”
Section: Introductionmentioning
confidence: 99%